Maternal characteristics and nutritional status among 6–59 months of children in Ethiopia: further analysis of demographic and health survey - Dessie, Zufan Bitew (BMC Pediatr, 2019)
BACKGROUND: Nutritional status of children influences their health status, which is a key determinant of human development. In Ethiopia, 28% of child mortality is caused by under nutrition. There is also some controversial evidence about the association between maternal characteristics and nutritional status of under five children. This study was aimed to assess the association between maternal characteristics and nutritional status among 6–59 months of children in Ethiopia. METHODS: This was furtheranalysis ofthe 2016 Ethiopian Demographic and Health Surveyusing7452 children.. Generalized estimating equations was used to quantify the association of maternal factors with stunting and wasting. Both crude Odds ratio and adjusted odds ratio with the corresponding 95% confidence intervals were reported to show the strength of association. In multivariable analysis, variables with a p-value of < 0.05 were considered statistically significant. RESULTS: The higher odds of stunting were found among children whose mothers had no education (AOR = 1.58; 95%CI: 1.25, 2.0) and primary education (AOR = 1.42; 95%CI: 1.13, 1.78), underweight nutritional status (AOR = 1.59; 95%CI: 1.27, 2.0), and anemia (AOR = 1.16; 95%CI: 1.04, 1.30). Similarly, higher odds of wasting were observed among children whose mother had underweight nutritional status (AOR = 2.34; 95%CI: 1.65, 3.38), delivered at home (AOR = 1.31; 95%CI: 1.07, 1.60), and lower than 24 months birth interval (AOR = 1.31; 95%CI: 1.04, 1.64). CONCLUSION: Maternal education, nutritional status, and anemia were associated with child stunting. Also maternal nutritional status, place of delivery, and preceding birth interval were associated with wasting. Therefore, there is needed to enhance the nutritional status of children by improving maternal underweight nutritional status, maternal educational and maternal anemia status, prolonging birth interval, and promoting health facility delivery.